MSD1 regulates pedicellate spikelet fertility in sorghum through the jasmonic acid pathway - Yinping Jiao (Nature Portfolio, 2018)
Inflorescence architecture affects crop grain yield. Here, the authors deploy whole-genome sequencing-based bulk segregant analysis to identify the causal gene of a sorghum multi-seeded (msd) mutant and suggest MSD1 regulating the fertility of the pedicellate spikelets through jasmonic acid pathway.